2013
DOI: 10.7243/2053-5775-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Salivary inflammatory mediators and metalloproteinase 3 in patients with chronic severe periodontitis before and after periodontal phase I therapy

Abstract: Background: The role of IL-1β, PGE 2 and MMP-3 in the pathogenesis of periodontal disease is well researched. This study aimed to asses and compared the salivary IL-1β, PGE 2 and MMP-3 levels in patients with untreated chronic severe periodontitis and those treated with periodontal phase I therapy and periodontally healthy individuals as controls, in relationship to the presence of salivary anti-β 1 IgA. Methods: A total of 30 subjects participate in the study: 15 subjects had chronic severe periodontitis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Inflammatory mediators play an important role in several chronic disorders 1 . The biologic events associated with inflammation also play an important role in the pathogenesis of chronic periodontitis (CP), which is characterized by the presence of pathogenic bacteria, breakdown of the connective tissue in tooth attachment, and resorption of alveolar bone 2,3 . Severe forms of CP affect ≈10% to 15% of the population of the developed world and are a major cause of tooth loss in adults 4,5 .…”
Section: Methodsmentioning
confidence: 99%
“…Inflammatory mediators play an important role in several chronic disorders 1 . The biologic events associated with inflammation also play an important role in the pathogenesis of chronic periodontitis (CP), which is characterized by the presence of pathogenic bacteria, breakdown of the connective tissue in tooth attachment, and resorption of alveolar bone 2,3 . Severe forms of CP affect ≈10% to 15% of the population of the developed world and are a major cause of tooth loss in adults 4,5 .…”
Section: Methodsmentioning
confidence: 99%
“…Microbial toxins have shown to stimulate various inflammatory mediators, including Interleukin-1β and tumor necrosis factor-α. IL-1β levels in gingival crevicular fluid (GCF) of individuals with periodontitis were significantly higher than those in healthy individuals in previous studies [24,25]. A series of events are associated with the high levels of cytokines released, which influences the stages of periodontitis.…”
Section: Discussionmentioning
confidence: 93%
“…Among the recruited participants in the study, significantly different periodontal inflammatory parameters were observed among the periodontitis patients. A study by Sánchez recruited 72 participants, including healthy individuals and cases with initial, moderate and severe forms of periodontitis [ 25 ]. They showed significant variation among healthy, moderate and severe periodontitis cases.…”
Section: Discussionmentioning
confidence: 99%